Analysis of the Implementation of Standard Operating Procedures (SOP) in the Housekeeping and Front Office Department of Frii Bali Echo Beach Hotel Canggu - Suwitra Wirya, I Made (Jurnal Manajemen Pelayanan Hotel, 2023)
This research is qualitative research. Data collection from this study used observation, interview and documentation methods. This study aims to analyze the standard operating procedures (SOPs) made and set by hotel management and analyze how the implementation of these SOPs is carried out and adhered to in the housekeeping and front office department of FRii Bali Echo Beach Canggu Hotel. SOP is a guideline that contains operating procedures in an organization or company that is used to ensure the validity of all decisions and actions, as well as the process of using company facilities. This qualitative research refers to 7 main things in standard operating procedures (SOPs) which include efficiency, consistency, minimizing errors, problem solving, labor protection, work maps and defense limits. Research informants were 4 people, namely, housekeeping managers, front office managers and 2 employees (1 housekeeping employee and 1 front office employee). Data collection techniques through interviews. The results of the analysis showed that the housekeeping and front office employees had carried out standard operating procedures (SOPs) set by the management of FRii Bali Echo Beach Canggu Hotel. As for the main things in the SOP for housekeeping and front office, there are several shortcomings, namely efficiency and protection of labor (employees) in the SOP housekeeping (HK). And there are shortcomings in the problem solving section and work map in the front office (FO) department. Keywords: Standard operating procedures, efficiency, consistency, minimizing work errors, problem solving, labor protection, workmap and defense limitations. Keywords: Standard operating procedures, efficiency, consistency, minimizing work errors, problem solving,labor protection, workmap and defense limitations.